Acute Oral Toxicity Classification Of Physalis minima Leaves Crude Water Extract Using The OECD TG423 On Female Sprague Dawley Rats - Lokman, Nur Afiqah (2015)
The leaves of Physalis minima commonly known as “Daun Letup-letup” is a plant which is commonly used by the local community in Malaysia as a natural remedy in folk medicine and possess several bioactivities. P. minima exhibited a wide range of biological and pharmacological activities in a few laboratories studies and believed to have system of medicines for nervous disorder, epilepsy, liver antioxidant, antiinflammation, analgesic, antipyretic and as a helpful remedy in ulceration of the bladder.